MySD: A Smart Social Distancing Monitoring System - Rusli M.E.; Yussof S.; Ali M.; Abobakr Hassan A.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Behavioral research; Smartphones; Bluetooth transceivers; Direct impact; Hardware features; Innovative solutions; Monitoring system; Safe distance; Social distance; Radio transceivers